PERAN CELEBRITY ENDORSER PADA KEPUTUSAN PEMBELIAN PRODUK ASURANSI AIA CABANG SOLO - Magdalena Nany; Lyna Lyna (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2023)
Restrictions on community activities caused by pandemic Covid-19 hit Indonesian economy. So do the insurance companies that sell tersier products with celebrity endorser Data were collected by questionnaires distributed by google form to the 100 respondents buying insurance products during the pandemic covid-19. Multiple regression analysis was used to analyze data. The results show that partially visibility, credibility and power significantly influenced purchasing decision. The results also show that partially attraction insignificantly influenced purchasing decision. Simultantly visibility, credibility, attraction and power significantly influenced purchasing decision